Self-Acceptance in Female Correctional Inmates in Class II B Kebumen State Prison - Nadikohtun Khalalia; Lutfi Faishol (Faculty Ushuluddin, Adab and Dakwah UIN Palangka Raya, 2025)
This study discusses self-acceptance in female correctional inmates (WBP) in the Kebumen Class IIB State Prison. Self-acceptance is an important factor that affects the mental and emotional well-being of women, especially in the face of social stigma, loss of freedom, and psychological pressure during the detention period. This study uses qualitative methods to explore factors that affect self-acceptance, such as social support, psychological conditions, and self-confidence. The study results show that social support from family, fellow inmates, and correctional officers plays a significant role in forming better self-acceptance. In addition, the age and duration of the sentence also affect a person's level of self-acceptance. Some WBPs, especially those new to detention, still have difficulty accepting their condition. Therefore, rehabilitation programs that strengthen psychological and social aspects are essential to help WBPs develop better self-acceptance.